A distribuição espacial do seguro rural no Brasil - Mendonça, Walef Machado De (2022)
Agricultural activities are part of a context of adversities that place them in a different situa- tion in relation to the risks faced by the producers. Such activities require large investments, which makes their attractiveness related to existing forms of risk management. One of the usual forms of risk management in this sector is the contracting of rural insurance, since this type of insurance makes it possible to recover the financial capacity of the producer in the event of accidents. In this way, the objective of this research is to analyze the distribution and spatial dynamics of variables related to rural insurance policies contracted in Brazilian municipalities from 2006 to 2019. To this end, the dissertation was divided into two articles. In the first, the objective is to evaluate the evolution of variables related to rural insurance individually. To this end, a descriptive analysis of the evolution of rural insurance policy variables was carried out. The results indicate that the highest concentrations of rural insurance policies are located in the South, Southeast and Midwest regions. In the second article, the objective is to inves- tigate the spatial distribution of rural insurance in Brazilian municipalities in the period from 2006 to 2019. To achieve this objective, Principal Component Analysis was used, in order to reduce the dimensionality of the data. The scores of the first principal component were used in Exploratory Spatial Data Analysis to investigate the presence of spatial distribution patterns in multivariate rural insurance data. The results indicate that the highest concentration of rural insurance policies are located in the South, Southeast and Midwest regions. In addition, despite an increase in rural insurance contracts, there is also a trend of greater spatial concentration of policies over the period. In both articles data from the Rural Insurance Census were used, com- piled by the Ministry of Agriculture, Livestock and Supply, and data with geographic attributes of the territory available at the website of the Brazilian Institute of Geography and Statistics.